Development of a phosphate based glass product for trace mineral supplementation in ruminants - Cartlidge, Ellena Amiee (2022)
Optimisation of agricultural practises is essential to feed a growing global population. One method commonly used by farmers to improve livestock production outputs is the administration of mineral supplements. Delivering minerals using a bolusing method enables consistent, reliable long-term mineral supplementation of livestock whilst grazing at pasture. However, this technique heavily relies on the bolused mineral supplement delivering minerals predictably and reliably across a known duration of time. Studies assessing the mineral boluses currently commercially available in the UK suggests that their ion release is not consistent across the complete product lifespan. Therefore, there is a need to develop a bolus that meets the requirement for a reliable, long term ion supplement with consistent ion release. The principle aim of this research was to develop a phosphate-based glass supplement to prevent trace mineral deficiency in ruminants through sustained mineral release over a 6-month period. A secondary aim of this research was to conduct competitor analysis on a commercially available phosphate-based bolus for mineral supplement in ruminants. These two main objectives were explored by trialling multiple different product designs and phosphate glass formulations. Designs and formulations were assessed through physical characterisation techniques including differential scanning calorimetry, x-ray diffraction, energy-dispersive x-ray spectroscopy, ash fusion testing and degradation studies to assess in vitro ion release. As a result of extensive testing the glass formulation a sintered phosphate-based glass bolus with the formulation P50-Ca2-Na17-Cu30-Co1 was trialled in vivo over a 1-month and compared to the ion release profiles obtained from the in vitro studies using rumen fluid and blood plasma mineral concentrations to assess degradation. Functional biochemical indicators such as Vitamin B12 were also used to assess mineral bioavailability, providing a more complete picture. These studies found that the proposed glass formulation (P50-Ca2-Na17-Cu30-Co1) did not adequately match the suggested Industry Partner’s ideal daily ion release requirements as it degraded significantly slower than expected, likely as a result of the in vitro simulation conditions not replicating in vivo conditions closely enough. In addition to the development of a novel bolus, the assessment of a commercially available phosphate-based bolus for mineral supplementation in ruminants was conducted to gain clarity into the degradation and ion release profile of this product in vivo. It was found that this bolus successfully supplemented cobalt, selenium and iodine, significantly elevating key biochemical indicators such as glutathione peroxidase. This research generated new knowledge surrounding phosphate based glass formulations and in vivo simulation techniques. However, this work also highlighted the complexities of developing a multi-faceted, long term supplement product designed for in vivo use. As such, key areas of further work were highlighted, which include bolus prototype production improvement and experimental in vivo simulation refinement.